Examining the Reporting Mechanism for Sexual Harassment at the Workplace : A Focus on Section 6 of the Kenyan Employment Act (Strathmore Law Review, 2020)
Sexual harassment in the workplace refers to any unwanted sexual request or advances by employers or colleagues. It is prevalent in the Kenyan context. Despite this, many cases of sexual harassment go unreported. This article looks at the factors affecting the reluctance to report sexual harassment in relation to the structure of the reporting mechanism under the Kenyan Employment Act. It is suggested that there exists a nexus between these factors and the structure of the reporting mechanism. This article is informed by the dominance feminism theory which identifies dominance as the basis for sexual harassment. To improve reporting, this article recommends increasing reporting avenues by including a commission and promoting training of employees on sexual harassment. With the exception of case law and statute, much of the information gathered has been sourced from books, papers, case law and published journals.